Formação do professor de língua inglesa no curso de licenciatura: novos rumos - Xavier, Jean Paulo Bernardo (2011)
This research argues about the English Teacher formation at the Letter graduation course at college. My professional trajectory and the students´questions about the pedagogical practice used by their English teachers, lead me to question the formation the future teachers get at the graduation course at college. The main objective of the research is to investigate the formation process the students get at the English and Literature course. The study will be held in a public college located in the seashore of Paraná State, from 2000 to 2008. They study will analise the changes occurred in the two last curricular board used in the graduation course. The first from 1997 and the second from 2005. The research will investigate the impact of the Especific Content Disciplines and the Pedagogical Formation Disciplines on the formation of the English teacher, according to the view of the ex-students of the institution in the period studied and nowadays teach English in regular schools. The study will also try to point the following objectives: verify the changes related to the amount of hours study and the insertion of new disciplines in the curricular boards, analyse what was the contribution of the knowledge the students get during their graduation course for their formation and their pedagogical practice. The study presents a qualitative approach. We used as methodological procedures: recorded interviews for a group of eighteen English teachers who graduated at the institution studies and stated their opinions about their formation. After carrying out the interviews analyses, we selected the categories based on the questions used for the interviews. The analyses show that few changes occurred in the course and the alterations implanted didn´t allow to form a competent and more prepared English teacher to face the reality of a teaching class. Of course, we are aware that not only the graduation course is responsible for this formation, but we learned that new changes may be made, so that we can have a better English teaching quality in our community.